Sistem Kontrol Otomatis Toren Air Berbasis Internet of Things (IoT) pada Wisma ITERA - Sabar Sabar; Joni Joni; Kisna Pertiwi; Rhahmi Adni Pesma; Yusuf Affandi; Achmad Chalid Afif A; Sitronella Nurfitriani hasim; Novalia Pertiwi (Jurnal Teori dan Aplikasi Fisika, 2026)
This research aims to automatically control electric pumps and monitor the condition of the on/off position of electric pump equipment on the ITERA campus using a smartphone or website. This research also to implement an Automatic Water Tower Control System as part of efforts towards a Smart Green Campus at the Sumatra Institute of Technology (ITERA). This system is designed using the Internet of Things (IoT) concept to automatically control water pumps in the parking area and Wisma ITERA. The testing stages include laboratory scale, limited space scale, and field implementation to ensure the accuracy of system input, process and output parameters. It is hoped that the implementation of this system can help save electrical energy in the campus environment and solve problems related to water management at Wisma ITERA. These steps are part of ITERA's commitment to become an environmentally friendly science and technology center and prepare human resources who are ready to compete nationally and internationally.     Keywords: Automatic Control System, Water Tower